Errors That Occur from Using an Inappropriate Thermal Buffer When Monitoring the Storage Conditions of Temperature Sensitive Products: Size and Material DO Matter - Michael Richard Rusnack (University of Minnesota Libraries Publishing, 2018)
Common practice in the monitoring of cold chain conditions for temperature sensitive products is to employ a physical thermal buffer into which the temperature probe is inserted. This buffer may be a bottle of glycol or other liquid, a container of glass beads, aluminum block or nearly any other media the user feels appropriate. The purpose of the buffer is to simulate the experience of the stored product rather than the air temperature. Obviously, this mission will not be accomplished to the extent that the physical buffer is not matched to the thermal properties of the stored product and its container. Cold chain managers are faced with a complex problem if they attempt to take this issue into account. Furthermore, a match is not possible with a single physical buffer when the cold storage unit contains different products or size containers. This paper quantifies the results of this mismatch from various factors and suggests possible solutions to this dilemma.   Type: Original Research